Gender disparity in Indian library and information science journals: An analytical study - Shiva Kumara, S U; Sampath Kumar, B T (Iberoamerican Journal of Science Measurement and Communication, 2025)
Objective. This study investigates gender disparity in research productivity in Indian Library and Information Science (LIS) journals, focusing on authorship patterns, professional engagement, prolific institutions, and regional productivity. Methodology. We analyzed 2404 articles with 4583 authors from ten selected Indian LIS journals (2014–2023). Author details, including gender, institutional affiliation, and authorship roles, were collected from biographical notes and recorded in Excel sheets. The analysis involved descriptive statistics and inferential tests (Chi-square tests and correlation analysis) using SPSS software. Findings. The study revealed a significant gender disparity in Indian LIS research, with male authors representing 71.81% of contributions and dominating first authorship roles (69.3%). Collaborative authorship patterns were also male-dominated, with male-only and male-majority teams prevailing. Faculty members of the University of Delhi and Aligarh Muslim University emerged as the top contributors. Female representation was more visible among research scholars in the KELPRO journal, which showed a balanced gender representation. Regional analyses showed that contributions from New Delhi, West Bengal, and Karnataka were the highest, with minimal representation from states such as Sikkim and Nagaland. Conclusions. This study highlights the persistence of gender disparity in Indian LIS scholarship and provides valuable insights into authorship dynamics, institutional productivity, and regional representation. These findings offer actionable recommendations for fostering inclusivity and gender equity in Indian LIS research.